Comparative study on mechanical properties of undoped and Ce-doped Bi-2212 superconductors - Zalaoğlu, Yusuf; Bekiroğlu, Erdal; Doğruer, Musa; Yıldırım, Gürcan; Öztürk, Özgür; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2013)
This study discusses the mechanical performances of Bi1.8Sr2.0CexCa1.1Cu2.1Oy ceramics with x = 0, 0.001, 0.003, 0.005, 0.01, 0.03, 0.05 and 0.1 by way of Vickers microhardness (H v ) measurements performed at different applied loads in the range of 0.245–2.940 N. For the potential industrial applications, the important mechanical characteristics such as Vickers microhardness, elastic modulus, yield strength, fracture toughness and brittleness index values of the samples studied are extracted from the microhardness measurements. All the results obtained indicate that the Vickers hardness, Young’s (elastic) modulus, yield strength, fracture toughness and brittleness index values suppress with the increment of the Ce concentration in the system as a consequence of the degradation in the connectivity between superconducting grains. The decrement in the H v values with the applied load is attributed Indentation Size Effect behaviour of the samples studied. Moreover, the experimental results of Vickers microhardness measurements are estimated using the 5 different models such as Kick’s law, proportional sample resistance model, modified proportional sample resistance model, elastic/plastic deformation model and Hays–Kendall approach. According to the results obtained from the simulations, Kick’s law is not useful model to obtain information about the origin of the indentation size effect feature of the Ce-doped bulk Bi-2212 superconductors. On the other hand, the Hays–Kendall approach is determined as the most suitable model for the description of the mechanical properties of the superconducting samples. In addition, the bulk porosity analysis for the samples reveals that the porosity increases monotonously with the Ce inclusion in the Bi-2212, leading to the degradation of the grain connectivity.